1993
DOI: 10.1073/pnas.90.8.3516
|View full text |Cite
|
Sign up to set email alerts
|

MCL1, a gene expressed in programmed myeloid cell differentiation, has sequence similarity to BCL2.

Abstract: During their lifespan, immature cells normally pass through sequential transitions to a differentiated state and eventually undergo cell death. This progression is aberrant in cancer, although the transition to differentiation can be reestablished in inducible leukemia cell lines. This report describes a gene, MCLl, that we isolated from the ML-1 human myeloid leukemia cell line during phorbol ester-induced differentiation along the monocyte/macrophage pathway. Our results demonstrate that expression ofMCLI in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
678
0
7

Year Published

1996
1996
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 876 publications
(707 citation statements)
references
References 40 publications
19
678
0
7
Order By: Relevance
“…We found that overexpression of Mcl-1 protected CE81T/VGH cells from staurosporine-induced apoptosis and transfection of a Mcl-1 antisense plasmid substantially increased the percentage of apoptotic cells (Figure 7). Our data support the fact that Mcl-1 is an inducible, antiapoptotic protein, as previously described in myeloid cells induced by TPA and GM-CSF (Kozopas et al, 1993;Chao et al, 1998), and in EBV immortalized B cells induced by IL-6 (Altmeyer et al, 1997). While the induction of Mcl-1 by TPA was mediated through the MAP kinase pathway in myeloblastic leukemia cells (Townsend et al, 1998), the IL-3 activation of mcl-1 gene expression was mediated via PI3-K-Akt-dependent andindependent pathways in murine pro-B Ba/F3 cells (Wang et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…We found that overexpression of Mcl-1 protected CE81T/VGH cells from staurosporine-induced apoptosis and transfection of a Mcl-1 antisense plasmid substantially increased the percentage of apoptotic cells (Figure 7). Our data support the fact that Mcl-1 is an inducible, antiapoptotic protein, as previously described in myeloid cells induced by TPA and GM-CSF (Kozopas et al, 1993;Chao et al, 1998), and in EBV immortalized B cells induced by IL-6 (Altmeyer et al, 1997). While the induction of Mcl-1 by TPA was mediated through the MAP kinase pathway in myeloblastic leukemia cells (Townsend et al, 1998), the IL-3 activation of mcl-1 gene expression was mediated via PI3-K-Akt-dependent andindependent pathways in murine pro-B Ba/F3 cells (Wang et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…As shown in Figure 1, we observed a dramatic increase in both MCL1 transcripts in ML-1 cells (3.8 and 2.4 kb; Kozopas et al, 1993). We also observed an increase in the WMN Burkitt's lymphoma cell line, which is similar to ML-1 in that p53 is wildtype and the cells respond to IR with increases in GADD45 and BAX (Zhan et al, 1996).…”
Section: Resultssupporting
confidence: 63%
“…Under both di erentiation-inducing and cytotoxic conditions, the expression of MCL1 increased rapidly, elevation of the MCL1 mRNA being seen within 1 ± 3 h and that of the protein at 3 ± 6 h (Kozopas et al, 1993;. The increase in MCL1 preceded di erentiation or death, which were detectable morphologically within 1 day and continued over approximately 3 days.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This implies the existence of other gene family members also involved in the regulation of apoptosis. A number of other cellular proteins including Bax (Oltvai et al, 1993), Bcl-x (Boise et al, 1993), Bak (Chittenden et al, 1995;Kiefer et al, 1995), Mcl-1 (Kozopas et al, 1993) and A1 (Lin et al, 1993) share highly conserved domains (BH-1 and BH-2; Oltvai et al, 1993) with Bcl-2. Bax is capable of forming homodimers and heterodimers with Bcl-2.…”
Section: Melanoma; Fish Analysismentioning
confidence: 99%